Analisis Minat Berkunjung Kembali Generasi Z ke Objek Wisata Mifan Waterpark Pada Masa Adaptasi Kebiasaan Baru - Muhammad Difa Naufal Abiyyu; Syevira Putri Gusti Amanda; Yusnateti Yusnateti; Dwi Pratiwi Wulandari (Nawasena: Jurnal Ilmiah Pariwisata, 2023)
This study aims to analyze Gen Z's intention to return to the Mifan Waterpark tourist attraction during the adaptation period to new habits. Gen Z is an important group in the tourism industry, and understanding their interest in visiting tourist attractions during the period of adapting to new habits is crucial for developing an effective marketing strategy. The survey method was used to collect data from Gen Z respondents who had visited Mifan Waterpark before. Data were analyzed using descriptive statistical techniques. The results showed that Gen Z had a high interest in visiting Mifan Waterpark again during the adaptation period to new habits, with an average respondent achievement rate of 79.41%. These findings indicate that efforts to manage and adjust Mifan Waterpark in dealing with adaptation to new habits have succeeded in attracting the interest of Gen Z. The practical implications of this research are the need to focus on increasing visitor satisfaction, adapting new habits continuously, using technology and social media, and developing experiences. unique to sustaining Gen Z interest in revisiting. This research provides valuable insights for the tourism industry in understanding the preferences and behavior of Gen Z consumers and determining appropriate strategies to attract and maintain their interest in the adaptation period to new habits.